Implementation of Sharia Principles in Microfinance: A Case Study in Indonesia - Agustina, Putri (Journal of Islamic Economy, 2024)
The purpose of this study is to analyze the implementation of sharia principles in microfinance in Indonesia through the Systematic Literature Review (SLR) approach. The SLR method was chosen because it allows researchers to collect and analyze various related literature systematically, in order to provide a comprehensive picture of the implementation of sharia principles in the microfinance sector in Indonesia. This study identifies relevant literature based on inclusion and exclusion criteria, focusing on studies published in the last 4-5 years that discuss the implementation of sharia principles in microfinance. Furthermore, a thematic analysis was conducted to identify patterns, trends, and challenges faced by sharia microfinance institutions in implementing sharia principles. The results of this study indicate that the implementation of sharia principles in microfinance in Indonesia has great potential to improve the economic welfare of the community, especially in terms of financial inclusion. However, significant challenges related to the community's understanding of sharia principles and the lack of supporting regulations are still major obstacles to its development. Nevertheless, sharia microfinance continues to show great potential in providing solutions for community economic empowerment. This study suggests the need for strengthening policies, increasing public education on sharia principles in microfinance, and product and service innovations that are more in line with market needs. The successful implementation of sharia principles is highly dependent on effective collaboration between financial institutions, government, and the community.